2017
DOI: 10.1016/j.jvir.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Medications That Improve Survival after Locoregional Therapy

Abstract: Purpose To determine if outpatient medications taken at the time of liver tumor embolization or ablation affect survival. Methods An IRB-approved retrospective review was performed of 2032 liver tumor embolization, radioembolization, and ablation procedures on 1092 patients from June 2009 to April 2016. For each patient, the following information was analyzed: pathology, hepatocellular carcinoma (HCC) stage (AJCC), neuroendocrine tumor (NET) grade, initial locoregional therapy, overall survival after initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…This HIPAA-compliant retrospective study received institutional review board approval. A previously reported retrospective review [2] had identified 304 consecutively registered patients with HCC (232 [76%] men, 72 [24%] women; mean age at embolization, 69 years) who were treated with TAE between June 2009 and April 2016. Further analysis of this group of patients was conducted in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This HIPAA-compliant retrospective study received institutional review board approval. A previously reported retrospective review [2] had identified 304 consecutively registered patients with HCC (232 [76%] men, 72 [24%] women; mean age at embolization, 69 years) who were treated with TAE between June 2009 and April 2016. Further analysis of this group of patients was conducted in the current study.…”
Section: Methodsmentioning
confidence: 99%
“…Retrospective studies have shown that aspirin use is associated with improved survival when combined with transarterial chemoembolization [1] or transarterial embolization (TAE) [2] for hepatocellular carcinoma (HCC). Several theories have been proposed to explain these results [2]. First, aspirin is antiinflammatory.…”
mentioning
confidence: 99%
“…Treatment toxicity could play a role, but in our study, there was no difference in complications between the two groups. Another possibility is that locoregional therapy can induce systemic effects that might counter the local benefits of the treatment [15]. One promising approach for improving survival (not just response) after locoregional therapy is the use of adjuvant medications that modulate these harmful systemic effects [15; 16].…”
Section: Discussionmentioning
confidence: 99%
“…We thank Dr. Jiang for the interest in our paper [1], where we showed that aspirin was associated with improved survival when taken at the time of initial embolization for HCC.…”
mentioning
confidence: 99%
“…Starting HCC patients on aspirin 81 mg daily before TACE or TAE might be beneficial, based on the evidence presented in our paper [1], another retrospective study showing improved survival when combining aspirin and TACE for HCC [2], a retrospective study showing that aspirin reduces both the risk of developing HCC and the risk of death from chronic liver disease [3], and randomized trials showing that aspirin decreases the risk of death from various adenocarcinomas [4]. Caution should be exercised if the patient has peptic ulcer disease, high risk of bleeding, or another contraindication to aspirin.…”
mentioning
confidence: 99%